ANALISIS STRUKTUR BAWAH PERMUKAAN DENGAN MENGGUNAKAN METODE SEISMIK REFRAKSI DI UNIVERSITAS TADULAKO - Adnyawati, Ni Ketut; Efendi, Rustan; Sabhan, Sabhan (Natural Science: Journal of Science and Technology, 2012)
The method is one of the seismic refraction geophysical methods that can be used to determine the structure of the subsurface. The purpose of this study was to to determine the subsurface structure in the area Tadulako University. In this method, the waves generated on the surface of the Earth that will reach down into the surface of the soil or rock, then disuatu point of the boundary between two layers of rock wave is reflected back to the surface and partially transmitted down some refracts due to changes in rock density. Wave propagation below the surface will be detected by the geophones. Aqusisi and data processing method Intercept Time. Data processing is done in 2 stages, using the program and program pickwin Plotreva. The end result of this data processing is the image of the subsurface profile Tadulako University of 6 stretch consisting of three layers of the same. The first layer has a wave speed (V1) 300 m/s are expected mixing of sand gravel dominated by gravel, the second layer has a wave velocity (V2) 1000 m/s are suspected of mixing sand gravel dominated by sand and the third layer has a velocity 2000 m/s are expected mixing of sand and clay.